2014
DOI: 10.1016/j.jand.2014.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable Consumption Is Linked to Decreased Visceral and Liver Fat and Improved Insulin Resistance in Overweight Latino Youth

Abstract: There is limited data on the impact of vegetable consumption on adiposity and metabolic health, specifically non-starchy vegetables (NSV) and vegetables that are dark green and deep orange/yellow (also known as nutrient-rich vegetables, NRV). This study examines the relationship between vegetable intake and adiposity, liver fat and insulin dynamics in overweight Latino youth. This cross-sectional study of 175 overweight (≥85th percentile BMI) Latino youth (8–18 years), with data collected 2006–2011, included t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 38 publications
2
37
0
1
Order By: Relevance
“…This strategy could play an important role in weight management. [79][80][81] In a cross-sectional study of 175 overweight Latino youth, nonstarchy vegetables consumption was associated with lower liver fat deposition, 82 increased insulin sensitivity and decreased visceral adipose tissue. Other observational studies supported the notion that NAFLD patients consume less vegetables and dietary fibers than controls.…”
Section: Fruits and Vegetablesmentioning
confidence: 99%
“…This strategy could play an important role in weight management. [79][80][81] In a cross-sectional study of 175 overweight Latino youth, nonstarchy vegetables consumption was associated with lower liver fat deposition, 82 increased insulin sensitivity and decreased visceral adipose tissue. Other observational studies supported the notion that NAFLD patients consume less vegetables and dietary fibers than controls.…”
Section: Fruits and Vegetablesmentioning
confidence: 99%
“…In a cross-sectional study in 175 Latino adolescents that included deep metabolic phenotyping, Cook et al (5) found that those who consumed the highest amount of non-starchy vegetables had a 44% lower hepatic fat content compared to those with the lowest intake (5.6±8.7% vs. 10.0±8.5%; p=0.01) (5). Nutrient-rich vegetable (leafy greens and green/orange vegetables) consumers had 31% greater insulin sensitivity and 17% less visceral adipose tissue compared to non-consumers (5).…”
Section: Fruit and Vegetable Intake Incident Type 2 Diabetes And Bimentioning
confidence: 99%
“…Nutrient-rich vegetable (leafy greens and green/orange vegetables) consumers had 31% greater insulin sensitivity and 17% less visceral adipose tissue compared to non-consumers (5). However, total vegetable intake was not associated with fasting glucose, fasting insulin, HOMA-IR, or insulin sensitivity and pancreatic beta-cell function as measured by clamp.…”
Section: Fruit and Vegetable Intake Incident Type 2 Diabetes And Bimentioning
confidence: 99%
See 1 more Smart Citation
“…Satu lagi penyelidikan telah menunjukkan hubungan yang positif antara pengambilan sayur-sayuran yang kaya dengan nutrien dengan sensitiviti insulin (Cook et al 2014). Kajian yang sama juga telah menunjukkan lemak viseral dapat dikurangkan dengan pengambilan sayur-sayuran yang kaya dengan nutrien.…”
Section: Pengambilan Sayur-sayuranunclassified